2019
DOI: 10.1155/2019/6045214
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nurse Led Intervention on Health Related Quality of Life among Children with Sickle Cell Disease in Oman: A Pilot Study

Abstract: Introduction. The children with Sickle Cell Disease (SCD) generally have poor Health Related Quality of Life (HRQOL). The study aimed to evaluate the effectiveness of nurse led intervention on HRQOL among children with SCD. Methods. A total of 30 samples were selected using convenient sampling. Children with SCD and their caregivers completed Pediatric Quality of Life Inventory (PedsQL) SCD-Module version 3.0. The nurse led intervention was given to the study group for 10 consecutive weeks. The control group r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Studies conducted in Oman and Iran focused on interventions designed to teach patients and caregivers how to manage and control the disease and the effect of such interventions on HRQOL ( 32 , 33 ). The 5A self-management model (Assess, Advise, Agree, Assistant, and Arrange) has been demonstrated to improve the quality of life of patients, as assessed through the Persian version of the SF-36 questionnaire administered before and after the administration of the 5A model ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted in Oman and Iran focused on interventions designed to teach patients and caregivers how to manage and control the disease and the effect of such interventions on HRQOL ( 32 , 33 ). The 5A self-management model (Assess, Advise, Agree, Assistant, and Arrange) has been demonstrated to improve the quality of life of patients, as assessed through the Persian version of the SF-36 questionnaire administered before and after the administration of the 5A model ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 5A self-management model (Assess, Advise, Agree, Assistant, and Arrange) has been demonstrated to improve the quality of life of patients, as assessed through the Persian version of the SF-36 questionnaire administered before and after the administration of the 5A model ( 32 ). Educational sessions on basic understanding of SCD and homecare management of signs and symptoms can significantly improve the HRQOL PedsQL score ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Pandarakutty et al reported that a nurse-led filial therapy and educational intervention resulted in a significant improvement in HRQOL scores among a group of children with SCD in Oman, particularly in terms of reducing emotions, improving knowledge, enhancing parental support and reinforcing family relationships. 65 i m p l i c at i o n s f o r f u t u r e r e s e a r c h The findings of this systematic review underline an urgent need for practical measures to improve the HRQOL of children and adolescents with SCD in the MENA region. Such initiatives should focus on increasing knowledge and awareness of SCD, developing support groups to enhance the psychological wellbeing of children and adolescents with SCD and their caregivers, mitigating the economic burden of care on the families of children with SCD and strengthening existing family, social and academic support systems.…”
Section: Discussionmentioning
confidence: 98%
“…reported that a nurse-led filial therapy and educational intervention resulted in a significant improvement in HRQOL scores among a group of children with SCD in Oman, particularly in terms of reducing emotions, improving knowledge, enhancing parental support and reinforcing family relationships. 65 …”
Section: Discussionmentioning
confidence: 99%